Synthesis of Iminonitriles by Oxone/TBAB-Mediated One-Pot Oxidative Three-Component Strecker Reaction - Gualtierotti, Jean-Baptiste; Schumacher, Xavier; Wang, Qian; Zhu, Jieping (Synthesis, 2013)
Oxidative three-component reaction of aldehydes, amines, and TMSCN in a biphasic solvent system (toluene/H2O) containing Oxone, tetra-n-butylammonium bromide (TBAB) and sodium bicarbonate afforded α-iminonitriles in good to excellent yields. This oxidative Strecker reaction was applicable to a wide range of aldehydes and amines, aromatic or aliphatic, of different electronic and steric properties. Substituted 1-aza-2-cyano-1,3-dienes were also accessible using α,β-unsaturated aldehydes as inputs.
Keywords: α-iminonitrile; Oxone; α-aminonitrile; oxidative three-component Strecker reaction; multicomponent reaction